2020
DOI: 10.1590/s1808-185120201901221678
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Development of the Spine and Spinal Cord in Human Fetuses

Abstract: Objective: The spinal cord extends from the foramen magnum to the sacrum in the human fetus at the beginning of the 2 nd quarter. However, the medullary cone is located at or above the level of the second lumbar vertebra at birth. The objective is to determine the difference between the rates of longitudinal growth of the spinal cord and the spine in human fetuses from the 13 th to the 22 nd week of gestation (WoG) using magnetic resonance imaging (MRI). Methods: Descriptive observational cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The studies that used post-mortem foetuses with either dissection 8 , 18 , 31 or post-mortem magnetic resonance 4 , 32 presented similar, low frequencies of foetuses with the CM at L2 from 19 to 25 weeks. In contrast, studies involving ultrasound performed on live foetuses 3 , 10 , 40 found that the CM was at L2 in approximately half of the entire sample of foetuses with gestational age from 19 to 25 weeks.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The studies that used post-mortem foetuses with either dissection 8 , 18 , 31 or post-mortem magnetic resonance 4 , 32 presented similar, low frequencies of foetuses with the CM at L2 from 19 to 25 weeks. In contrast, studies involving ultrasound performed on live foetuses 3 , 10 , 40 found that the CM was at L2 in approximately half of the entire sample of foetuses with gestational age from 19 to 25 weeks.…”
Section: Discussionmentioning
confidence: 86%
“…Regarding sexual dimorphism, despite the small number of studies that addressed this variable, no significant association was found among the articles included in the present review. Manzone et al 32 found no statistically significant difference in SC length between male and female foetuses in an Argentinian study performed with magnetic resonance. Perlitz et al 40 used ultrasound to analyse Israeli foetuses and also found no difference in CM position between the sexes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The growth of the vertebral column is faster than that of the spinal cord in developing fetuses, and the postnatal life spinal cord terminates early within the vertebral canal. This process is known as the ascent of the spinal cord, and this terminology has passed from one author to another [1]. The exact time of this ascent has not been determined [2].…”
Section: Introductionmentioning
confidence: 99%
“…The spinal cord generally starts to "ascend" after nine weeks, reaching the level of the last sacral piece around 12 weeks of age. The cord reaches the level of the lower border of the S1 at fifteen weeks, the lower border of the L4 at six months, and the lower border of the L3 at full term [1,[3][4][5]. During childhood, once the spinal cord has reached its definitive level, the spinal cord and the spine's growth continues at the same rate and rhythm until adulthood [5].…”
Section: Introductionmentioning
confidence: 99%